2015
DOI: 10.1038/srep15166
|View full text |Cite
|
Sign up to set email alerts
|

Are fish fed with cyanobacteria safe, nutritious and delicious? A laboratory study

Abstract: Toxic cyanobacterial blooms, which produce cyclic heptapeptide toxins known as microcystins, are worldwide environmental problems. On the other hand, the cyanobacteria protein (30–50%) has been recommended as substitute protein for aquaculture. The present laboratory study verified the feasibility of cyanobacteria protein substitution and risk assessment. Goldfish were fed diets supplemented lyophilised cyanobacteria powder for 16 weeks with the various doses: 0% (control), 10%, 20%, 30% and 40%. Low doses (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Because the pattern and quantity of essential amino acids strictly determines the nutritional value of protein food for humans, the decreased essential amino acids (including phenylalanine, histidine, isoleucine, leucine, lysine, methionine and threonine) and total essential amino acids suggested a declined nutritional value of blunt snout bream fillet caused by dietary toxic cyanobacteria and ammonia exposure. A similar result was achieved by Liang et al who reported significantly lower levels in total amino acids contents and almost all essential amino acids when goldfish were fed diets contained a high dose (30% and 40%) of cyanobacteria for 16 weeks.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Because the pattern and quantity of essential amino acids strictly determines the nutritional value of protein food for humans, the decreased essential amino acids (including phenylalanine, histidine, isoleucine, leucine, lysine, methionine and threonine) and total essential amino acids suggested a declined nutritional value of blunt snout bream fillet caused by dietary toxic cyanobacteria and ammonia exposure. A similar result was achieved by Liang et al who reported significantly lower levels in total amino acids contents and almost all essential amino acids when goldfish were fed diets contained a high dose (30% and 40%) of cyanobacteria for 16 weeks.…”
Section: Discussionsupporting
confidence: 84%
“…Feed ingredients were showed in Table . Based on the toxic cyanobacteria powder contents in our previous study, two isonitrogenous and isoenergetic diets were prepared. The control diet (TCP0) contained no toxic cyanobacteria powder, whereas the experimental diet (TCP30) contained 30% toxic cyanobacteria powder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water blooms caused by cyanobacteria are unfavorable especially for lakes used for water supply and for recreational purposes. They can pose a health threat owing to the potential production of toxins, which can lead to serious health problems [54][55][56][57]. An efficient method for removing cyanotoxins from water is essential [58].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, more than 100 analogues of MCs and about nine analogues of NODs [10,11,12] have been described in the literature. Toxic cyanobacteria frequently result in human health hazards and wildlife fatalities [13,14,15,16,17,18,19,20]. Nodularia spumigena was firstly reported in the literature as the toxic cyanobacterium for livestock [21].…”
Section: Introductionmentioning
confidence: 99%